Josefa Toledo de Aguerri and her educational ideas - Zosa-Cano, Alexander (2024)
In this essay, the author traces the long life of Josefa Toledo de Aguirre (1866-1962), a great Nicaraguan intellectual and educator woman, who made very important contributions for education and for women.